Dinamika Perguruan Tinggi Nusantara Di Tengah Arus Ekspansi Pendidikan Tinggi Global - Yohan Yohan (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
The expansion of global higher education is convincingly beginning to seep into higher education connections in Indonesia. Foreign universities access into Indonesia will be a kind of ‘contestational’ and ‘exotic’ journey heavenly for business profits of ‘global education capitalists’ networks which mainly focus on two main objectives: ‘teaching’ and ‘research’. On the contrary, it becomes a momentum for us to stimulate the development of domestic campuses in order to be more dynamic in welcoming opportunities and challenges to create and innovate relevantly to the demands and the needs of the people of Republic of Indonesia through solid coordinations and supervisions in encouraging and accelerating national development through the sense of Nusantara characters. Sooner or later, the expansive academic infiltration of global higher education is beginning to drive our higher educations to compete among the superiors. Thus, the government of Republic of Indonesia has to endorse the capability, credibility and accountability of higher education institutions through the common sense on the basic values of higher education as non-profit organization being mandated by our national constitutions and laws in intensifying community service and welfare. Make everything closer to the community, not by adopting randomly all commercial motives of global higher education which are capitalist and liberal sensed. To sum up, a set of pro-public rules, controls and policies must be strategically prepared with adequate supports based on scientific truths, benefits, reasonings, justice, virtue, affordability, honesty, sustainability, and religious responsibilities and social diversities. Keywords: Dynamics, Tri Dharma, Academic Community, Motivation and Academic Expansion, and Globalization of Higher Education Abstrak Perluasan pendidikan tinggi global secara meyakinkan mulai meresap ke dalam koneksi pendidikan tinggi di Indonesia. Akses universitas asing ke Indonesia akan menjadi semacam perjalanan 'kontroversial' dan 'eksotis' surgawi untuk keuntungan bisnis dari 'jaringan kapitalis pendidikan global' yang terutama berfokus pada dua tujuan utama: 'mengajar' dan 'penelitian'. Sebaliknya, itu menjadi momentum bagi kita untuk merangsang pengembangan kampus dalam negeri agar lebih dinamis dalam menyambut peluang dan tantangan untuk menciptakan dan berinovasi secara relevan dengan tuntutan dan kebutuhan masyarakat Republik Indonesia melalui koordinasi yang solid dan pengawasan dalam mendorong dan mempercepat pembangunan nasional melalui rasa karakter Nusantara. Cepat atau lambat, infiltrasi akademik yang luas dari pendidikan tinggi global mulai mendorong pendidikan tinggi kita untuk bersaing di antara para atasan. Dengan demikian, pemerintah Republik Indonesia harus mengesahkan kemampuan, kredibilitas dan akuntabilitas lembaga pendidikan tinggi melalui akal sehat pada nilai-nilai dasar pendidikan tinggi sebagai organisasi nirlaba yang diamanatkan oleh konstitusi dan undang-undang nasional kita dalam mengintensifkan pelayanan masyarakat dan kesejahteraan. Jadikan segalanya lebih dekat dengan komunitas, bukan dengan mengadopsi secara acak semua motif komersial pendidikan tinggi global yang bersifat kapitalis dan liberal. Singkatnya, seperangkat aturan, kontrol, dan kebijakan pro-publik harus dipersiapkan secara strategis dengan dukungan yang memadai berdasarkan pada kebenaran ilmiah, manfaat, pertimbangan, keadilan, kebajikan, keterjangkauan, kejujuran, keberlanjutan, dan tanggung jawab agama dan keragaman sosial.